High-carbon steel anti-decarburization coating as well as preparation method and application thereof

By reasonably selecting and proportioning SiO2, Al2O3, ZnO, SiC, B2O3 and other components in high-carbon steel anti-decarbonization coatings, and combining appropriate solvents and spraying technology, the problem of existing coatings being unable to cure quickly and glazed at high temperatures is solved, and the simplicity of rapid curing of coatings, low-temperature glazing and phosphorus removal is achieved, and the protection effect of steel is significantly improved.

CN119752225AActive Publication Date: 2025-04-04HUBEI XINGLONG HIGH TEMPERATURE ENERGY SAVING MATERIAL CO LTD +1

Patent Information

Application Number
CN202411750943.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-04-04
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

Existing anti-decarbonization coatings cannot achieve rapid curing at high temperatures, glaze formation and phosphorus removal at low temperatures are simple, cannot meet actual production needs, and there are corrosion and hole problems.

Method used

A high-carbon steel anti-decarbonization coating is used, and its composition includes SiO2, Al2O3, ZnO, SiC, B2O3 and other components. By controlling the Al/Si ratio and adding ZrO2 and other substances, a stable coating structure is formed, rapid curing and low-temperature glaze formation is achieved, and the simplicity of descaling is ensured through appropriate solvent composition and spraying technology.

Benefits of technology

The simplicity of rapid curing of the coating, low-temperature glazing and phosphorus removal is achieved, providing effective protection in the range of 700°C to 1300°C, and significantly improving the fatigue toughness and service life of the steel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119752225A_ABST
    Figure CN119752225A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of anti-decarburization coatings, in particular to a high-carbon steel anti-decarburization coating and a preparation method and application thereof. The coating disclosed by the invention is prepared from the following raw materials in parts by weight: 30 to 35 parts of SiO2, 4 to 6 parts of Al2O3, 0.5 to 1 part of talcum powder, 1 to 2 parts of gypsum powder, 1 to 5 parts of ZrO2, 1 to 3 parts of potassium feldspar powder, 1 to 3 parts of albite powder, 5 to 10 parts of ZnO, 1 to 4 parts of Cr2O3, 5 to 8 parts of SiC, 5 to 9 parts of B2O3, 1 to 4 parts of graphite and 30 to 40 parts of solvent. Wherein the ratio of Al to Si is 1: (6-8); the solvent is prepared from 0.1 to 0.6 percent of methyl cellulose, 5 to 10 percent of sodium silicate / potassium silicate, 0.3 to 1 percent of polyethylene glycol, 0.01 to 0.03 percent of hexadecyl sodium sulfonate and the balance of water. The coating provided by the invention has the advantages of rapid curing, low-temperature glazing and simple phosphorus removal.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-decarburization coatings, and in particular to a high-carbon steel anti-decarburization coating and a preparation method and application thereof. Background Art

[0002] Decarburization often occurs in steel materials during hot processing. In a high temperature environment above 1000 degrees, the oxidizing atmosphere in the furnace constantly interacts with the carbon in the surface layer of the metal matrix, resulting in a decrease in the carbon content of the outer layer of the steel. Due to the diffusion effect, the carbon in the inner layer of the billet continues to diffuse to the outer layer, which reduces the overall carbon content of the billet. The loss of carbon atoms directly leaves a decarburized layer with a significant gradient microstructure, and the corresponding mechanical properties also show gradient characteristics in the decarburized layer: in the topmost surface layer, the hardness value is the lowest and increases along the depth direction until the matrix. Moreover, parts produced from medium and high carbon steel are directly put into practical use after high temperature heat treatment. The surface decarburization phenomenon will cause serious damage to the fatigue toughness of the steel and reduce the fatigue limit by 50%. In addition, due to the difference in their expansion coefficients, different parts of the surface will generate stress during quenching, resulting in the generation of microcracks in the transition area between the decarburized layer and the partial decarburized layer on the surface of the medium and high carbon steel, which aggravates the failure of the components and affects the performance and service life of the steel.

[0003] In view of this problem, CN117304722A designed a coating material with phosphate as an adhesive to protect against oxidation and decarburization during high-temperature treatment. However, this coating uses a large amount of aluminum polyphosphate, which makes the coating acidic. This coating will cause serious corrosion to the metal body at high temperatures. At the same time, the aluminum polyphosphate formed after dehydration at high temperature is cross-linked with silicate, and the formed compound is not easy to descale, which will cause a large amount of oxide residue and reduce the surface quality of the material. The components used in CN107500790B include 15-25% graphite and 15-35% silicon carbide. The carbon content in the components is too high. Obviously, when oxidized at high temperature to generate carbon monoxide and carbon dioxide gas, a large number of holes will be generated in the coating, causing the coating to lose the ability to isolate the air and inhibit oxidation and decarburization. CN117511260A uses water as a solvent, which is difficult to ensure the curing speed. The coating in CN103757188A is composed of magnesium oxide, aluminum oxide, and calcium oxide. No substances are used to reduce the glazing temperature of the coating. The glazing temperature is above 800 degrees, but the steel billet has begun to decarburize at 700 degrees during the heating process. The MG90T coating used on the market has a glazing temperature higher than 700 degrees, and it is difficult to provide protection during the heating process from 700°C to 1000°C. At the same time, the above-mentioned several existing anti-decarburization coatings cannot simply complete the dephosphorization process. Usually, high-pressure water gun flushing of more than 30MPa is required to complete the dephosphorization, which cannot meet the production conditions of some manufacturers, greatly limiting the application and promotion of decarburization coatings. Therefore, the current existing technology cannot achieve the actual production needs of rapid curing, low-temperature glazing, and simple dephosphorization. Summary of the invention

[0004] The purpose of the present invention is to provide a high carbon steel anti-decarburization coating and a preparation method and application thereof in view of the above-mentioned deficiencies in the prior art.

[0005] A high carbon steel anti-decarburization coating of the present invention comprises the following raw materials in parts by weight:

[0006] SiO 2 30 to 35 parts, Al 2 O 3 4 to 6 parts, talcum powder is 0.5 to 1 part, gypsum powder is 1 to 2 parts, ZrO 2 1 to 5 parts, potassium feldspar powder is 1 to 3 parts, sodium feldspar powder is 1 to 3 parts, ZnO is 5 to 10 parts, Cr 2 O 3 1 to 4 parts, SiC 5 to 8 parts, B 2 O 3 5 to 9 parts, graphite is 1 to 4 parts, and solvent is 30 to 40 parts;

[0007] Among them, the Al / Si ratio is 1:6-8;

[0008] The solvent consists of 0.1-0.6% methyl cellulose, 5-10% sodium silicate / potassium silicate, 0.3-1% polyethylene glycol, 0.01-0.03% sodium hexadecyl sulfate and the balance water.

[0009] Furthermore, the density of the coating is 2.8×10 3 kg / m 3 ~3.0×10 3 kg / m 3 , and\or, the solid content is 60% to 68%.

[0010] A method for preparing the high carbon steel anti-decarburization coating as described above, comprising mixing and stirring the components according to the weight portions to obtain a powder, and stirring the powder and a liquid agent until a suspension is formed to obtain the high carbon steel anti-decarburization coating;

[0011] The preparation process of the liquid is as follows: after heating water, methyl cellulose, sodium silicate, polyethylene glycol and sodium hexadecyl sulfate are added in sequence, and stirred until no flocs are formed.

[0012] An application of the above-mentioned high carbon steel anti-decarburization coating comprises the following steps:

[0013] S1. Atomizing and spraying the coating on the surface of a high-carbon steel billet workpiece under a high-pressure air pump to form a coating;

[0014] S2, placing the sprayed and dried high carbon steel billet workpiece into a heating furnace, first slowly heating it to a preset temperature, and keeping it warm for a period of time;

[0015] S3. After the heat preservation is completed, the high carbon steel billet workpiece is taken out for descaling.

[0016] Furthermore, in step S1, the thickness of the coating is 200um to 500um; or, the amount of the coating is 0.2kg / m 2 ~0.6kg / m 2 .

[0017] Furthermore, in step S1, the temperature of the surface of the high carbon steel billet workpiece is 10°C to 750°C; or, the temperature of the surface of the high carbon steel billet workpiece is 30°C to 300°C.

[0018] Furthermore, in step S2, the insulation temperature is 1000-1300°C.

[0019] Furthermore, in step S2, in the heating furnace, the temperature is increased at a rate of 0.15-0.2°C / S, and the temperature is kept at a preset temperature for 1 hour.

[0020] Furthermore, in step S3, the specific operation of descaling is: using a high-pressure water gun to impact the steel billet with water for 3-5 minutes, the water pressure is 1-10 MPa, and after the water impact, the coating material is removed by beating.

[0021] The high carbon steel anti-decarburization coating of the present invention pays attention to the relationship between the composition and performance of the protective coating, mainly considers the components around solidification film formation, glaze protection and descaling, and achieves the purposes of rapid solidification, low temperature glazing and simple phosphorus removal.

[0022] The mass of ZnO is controlled to be 5-10 parts. ZnO is a strong flux, which can play a good fluxing role in a large range. At the same time, it can reduce the thermal expansion coefficient of the coating, resulting in a large difference in the thermal expansion coefficient between the coating and the steel. Moreover, as the temperature rises (the temperature reaches 1000℃), the 4-coordinated [ZnO 4 ] is transformed into a 6-coordinated [ZnO 6 ], due to [ZnO 6 ] has a sparse octahedral structure, so that the high-carbon steel billet coating provided in the present application can be easily fallen off under the impact of a water gun.

[0023] Control SiO 2 The mass of SiO is 30 to 35 parts. 2 It accounts for the majority of the film components. SiO 2 Can form a silicon-oxygen tetrahedral network structure, and an appropriate amount of SiO 2 It can combine with K and Na ions to form NaSiO and KSiO, which promotes film formation and gives the coating a certain gloss. However, too much SiO 2 The component will reduce the viscosity of the molten glass and cause the loss of the coating at high temperature.

[0024] Control Al 2 O 3 The mass is 4 to 6 parts, Al 2 O 3 It is an intermediate oxide that can react with SiO 2 Combined with alkaline oxides. During the glaze melting process, Al 2 O 3 It can often capture free oxygen to form a four-coordinated structure and enter the silicon-oxygen network, thus strengthening the glass network structure. 2 O 3 Due to its high stability and high melting point, it can form a stable phase with other oxide components, and the stable phase reduces the drastic changes in the melt. The temperature changes too quickly during the film formation process, which can easily generate bubbles, and Al 2 O 3It can make the temperature of the melt rise more steadily, thus helping bubbles to be better discharged during the firing process. It makes the film forming process more stable. 2 O 3 It not only improves the vitrification ability of the coating, but also inhibits the generation of bubbles and promotes the formation of a stable film.

[0025] The Al / Si ratio in the coating is maintained at 1:6-8. Within this range, the aluminum oxide hexahedron combines with the silicon oxide tetrahedron in the coating, which will reduce the expansion coefficient of the glaze layer and facilitate descaling. In addition, excessive silicon oxide will react with iron oxide to form ferrous silicate and ferrous silicate compounds. These compounds formed by the reaction are not easy to remove under the impact of the water gun. 2 The amount of SiO needs to be controlled. 2 It is conducive to the formation of the film. However, too much Al will cause the melting point of the coating material to rise, the coating film-forming temperature to increase, and it will not be able to complete the solidification at a low temperature, thus affecting the coating film-forming effect and anti-decarburization effect.

[0026] ZrO 2 The mass of ZrO is 5 to 7 parts, which has a very small linear expansion coefficient. 2 In the monoclinic phase, MgO provided by 0.5-1 parts by weight of talc and CaO provided by 1-2 parts by weight of gypsum powder are introduced by doping to form a solid solution of zirconium oxide, that is, microcrystalline zirconium silicate, so that ZrO 2 At 1170℃, it changes from monoclinic phase to tetragonal phase and remains relatively stable. Due to the phase change at 1100℃~1200℃, the volume of zirconium oxide expands, and its thermal expansion coefficient is also small, resulting in a certain gap between it and the steel substrate, which can make the coating cool and peel off by itself to achieve the purpose of descaling.

[0027] Control Cr 2 O 3 The mass of Cr is 1 to 4 parts. The Cr element has a strong affinity for metals and can form chemical bonds or ionic bonds with the metal surface, which helps to improve the adhesion between the film layer and the substrate, ensure that the film and the metal matrix have a certain bonding strength, provide the density of the film layer, reduce porosity and microcracks, and prevent external media (such as water, oxygen, etc.) from penetrating into the coating, further improving the performance of the film.

[0028] Control B 2 O 3 The mass of B is 5 to 9 parts. 2 O 3 It has the property of forming a glassy structure at high temperatures. Compared with other oxides, B 2 O 3The boron-oxygen bond in the molecule is relatively weak, making the molecular structure more flexible and forming an amorphous structure with a low melting point, which makes its melting point relatively low. At the same time, it reduces the original tight lattice structure by coordinating with metal ions in other oxides, and when it is combined with other high melting point oxides (such as SiO 2 、Al 2 O 3 After mixing with other materials (such as quartz and chlorinated polyols), the crystal structure of these oxides can be destroyed at a certain temperature, thereby reducing the melting point of the entire mixture. This allows the material to more easily transition from a solid state to a molten state at high temperatures, ultimately reducing the film-forming temperature and expanding the protective range of the coating.

[0029] The mass of SiC is 5 to 8 parts. SiC is a hard material that can improve the mechanical strength and wear resistance of the coating. In the process of transporting steel into the heating furnace, it can prevent the coating from being damaged due to vibration or other factors. At the same time, the surface reactivity of SiC is low and it is not easy to react directly with oxygen. It can effectively isolate the contact between oxygen and the steel surface, thereby enhancing its anti-decarburization effect. At high temperature, SiC will undergo the following reaction: SiC+O 2 =SiO 2 +C、C+O 2 =CO 2 These two reactions not only consume oxygen to achieve the purpose of anti-oxidation, but also generate SiO2, which promotes the formation of the film. 2 The generated C exists in two ways: one is to react with oxygen, and the other is to penetrate into the metal surface, which can achieve the purpose of anti-oxidation and carbon supplementation.

[0030] Sodium silicate / potassium silicate water glass is added to the controlled solvent. Water glass can quickly crystallize in the air, promote solidification, and reduce powdering. At the same time, weak alkaline solvents can ensure the viscosity of the coating, greatly increase the construction performance of spraying, and shorten the film-forming time. However, when the water glass content is too high, due to the introduction of too high potassium / sodium ions, it is easy to cause chemical corrosion to the surface of the steel billet, which is not conducive to the control of surface quality.

[0031] Controlling the content of sodium hexadecyl sulfonate in the solvent, this surfactant can remove the surface tension of water and activate the powder particles, thereby eliminating bubbles in the coating, improving the coating quality and shortening the film-forming time.

[0032] The beneficial effects of the present invention are as follows:

[0033] 1. The coating has excellent curing performance. After spraying, a glossy coating is formed on the surface of the high-carbon steel billet. The coating is firmly bonded to the surface of the high-carbon steel billet without powdering or cracking, and has a strong bonding force. At the same time, the curing speed after bonding is excellent, and the curing can be completed within 3 to 5 minutes to start protecting the surface of the steel billet.

[0034] 2. Compared with traditional anti-decarburization coatings, the high-carbon steel anti-decarburization coating of the present invention has a wider protection range. Specifically, it can provide effective protection effect until 1300 degrees after glazing at a low temperature of 700 degrees.

[0035] 3. After the high-temperature heat treatment is completed and the steel billet is out of the furnace, the bonding force between the coating and the surface of the high-carbon steel billet workpiece is weakened, and a high-pressure water gun is not required. The descaling rate of more than 95% can still be achieved at a descaling water pressure of 10MPa. Compared with the anti-decarburization products on the market, the descaling effect is obvious and the descaling effect is better.

[0036] 4. The coating has good suspension performance, long storage time, simple process and low cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 Surface images of the high carbon steel anti-decarburization coating provided in the embodiment of the present application and the MG90T high carbon steel coating on the market sprayed on 60Si-Cr high carbon steel before heat treatment;

[0038] Figure 2 Surface images of the high carbon steel anti-decarburization coating provided in the embodiment of the present application and the MG90T high carbon steel coating on the market sprayed on 60Si-Cr high carbon steel after heat treatment and finally descaling under 10MPa water pressure;

[0039] Figure 3 The metallographic cross-sections under optical microscope are respectively the high carbon steel billet workpiece treated in Example 1, the uncoated high carbon steel after dephosphorization after heat treatment, and the high carbon steel billet workpiece treated in Comparative Example 3. DETAILED DESCRIPTION

[0040] The following are specific embodiments of the present invention and the accompanying drawings to further describe the technical solution of the present invention, but the present invention is not limited to these embodiments.

[0041] Example 1

[0042] The application of high carbon steel anti-decarburization coating on high carbon steel billet workpiece (60Si-Cr) is as follows:

[0043] S1. Surface pretreatment of high carbon steel billet workpiece.

[0044] Use sandpaper to grind the surface of the high carbon steel billet workpiece to remove the oxide layer on the surface of the high carbon steel billet workpiece. After the surface of the high carbon steel billet workpiece is smooth, ultrasonic cleaning is performed on the high carbon steel. Keep the surface of the high carbon steel free of oil stains.

[0045] S2. Spray the surface of the high carbon steel billet and allow it to dry naturally.

[0046] Mix the coating evenly and make it viscous before atomizing and spraying. Use a high-pressure spray gun to spray it on the surface of the high-carbon steel billet. Control the viscosity to 100-150mPa·s before spraying it on the high-carbon steel surface. After spraying, place the high-carbon steel billet at room temperature to dry.

[0047] S3. Complete heat treatment

[0048] Put the sprayed and dried high carbon steel billet into the heating furnace, first slowly heat it to the predetermined temperature. The heating rate is 0.15-0.2℃ / S, and then heat it to the holding temperature of 1080 degrees and keep it for 1 hour. Then take out the high carbon steel billet for descaling.

[0049] S4. Descaling of high carbon steel billet workpieces

[0050] After the sample is taken out of the heating furnace, the steel billet is subjected to water jet impact for 3-5 minutes, and then knocked to remove the coating material. Finally, the high carbon steel billet workpiece is cleaned and dried.

[0051] Among them, the mass percentage of the coating is SiO 2 30 parts, Al 2 O 3 5 parts, talc is 1 part, gypsum powder is 1 part, ZrO2 is 1.5 parts, albite is 2 parts, potassium feldspar is 3 parts, ZnO is 6 parts, Cr 2 O 3 1 part, SiC 7 parts, B 2 O 3 The amount of tantalum is 7 parts, graphite is 4 parts, and the solvent is 35 parts.

[0052] The film formation is completed in 3 minutes, the film formation effect is good and glossy, the glazing temperature is 658 degrees, the descaling effect is excellent under 10MPa water pressure, the descaling rate is 96%, and there is no decarburization on the surface.

[0053] Example 2

[0054] The coating composition is different from that of Example 1, and the rest is the same as that of Example 1.

[0055] The mass percentage of the coating is SiO 2 30 parts, Al 2 O 3 5 parts, talc is 0.5 parts, gypsum powder is 2 parts, ZrO 2 1 part, Na feldspar 2 parts, K feldspar 3 parts, ZnO 7 parts, Cr 2 O 3 1 part, SiC 6.5 parts, B 2 O 3 The amount of tantalum is 9 parts, graphite is 2 parts, and the solvent is 35 parts.

[0056] The film formation is completed in 4 minutes with good film formation effect. The glazing temperature is 665 degrees. The descaling effect is excellent under 8MPa water pressure, the descaling rate is 92%, and there is no obvious decarburization on the surface.

[0057] Example 3

[0058] The coating composition is different from that of Example 1, and the rest is the same as that of Example 1.

[0059] The mass percentage of the coating is SiO 2 35 parts, Al 2 O 3 5 parts, talc 1 part, gypsum powder 2 parts, ZrO 2 3 parts, Na feldspar 1 part, K ​​feldspar 1 part, ZnO 9 ​​parts, Cr 2 O 3 1 part, SiC 5 parts, B 2 O 3 The amount of tantalum is 7 parts, graphite is 1 part, and the solvent is 37 parts.

[0060] The film formation is completed in 3 minutes with good film formation effect. The glazing temperature is 675 degrees. The descaling effect is excellent under 5MPa water pressure, the descaling rate is 91%, and there is no obvious decarburization on the surface.

[0061] Comparative Example 1

[0062] The coating composition is different from that of Example 1, and the rest is the same as that of Example 1.

[0063] The mass percentage of the coating is SiO 2 30 parts, Al 2 O 3 8 parts, talc 1 part, gypsum powder 1 part, ZrO 2 1.5 parts, sodium feldspar 2 parts, potassium feldspar 3 parts, ZnO 2 parts, Cr 2 O 3 1 part, SiC 7 parts, B 2 O 3 The amount of tantalum is 7 parts, graphite is 4 parts, and the solvent is 35 parts.

[0064] The film formation was completed in 8 minutes, the glazing temperature was 750 degrees, the descaling effect was average under the water pressure of 10MPa, the descaling rate was 80%, and there was no obvious decarburization on the surface. This is because the aluminum oxide content is too high, the glazing temperature is greatly increased, so the film formation speed is slow, and the descaling effect is average because the zinc oxide content is greatly reduced.

[0065] Comparative Example 2

[0066] The coating composition is different from that of Example 1, and the rest is the same as that of Example 1.

[0067] The mass percentage of the coating is SiO 2 45 parts, Al 2 O 3 5 parts, talc is 0.5 parts, gypsum powder is 2 parts, ZrO 2 1 part, albite 2 parts, potassium feldspar 3 parts, ZnO 7 parts, Cr 2 O 3 The amount of Ag is 6 parts, the amount of SiC is 6.5 parts, the amount of graphite is 2 parts, and the amount of solvent is 40 parts.

[0068] The film formation was completed in 10 minutes, the film formation effect was average, the glazing temperature was 770 degrees, the descaling effect was average under 10MPa water pressure, the descaling rate was 85%, and there was a full decarburized layer on the surface. This is because the silicon oxide content is too high, the ratio of aluminum oxide to silicon oxide is less than 1:8, resulting in average descaling effect of the coating, low viscosity of the coating, and the protective effect is affected. At the same time, the chromium oxide content is too high and does not contain boron, so the film formation speed is slow, which affects the descaling effect of the coating.

[0069] Comparative Example 3

[0070] The coating composition is different from that in Example 1, and MG90T coating on the market is used. The rest is the same as in Example 1.

[0071] The film formation was completed in 10 minutes, the film formation effect was average, the glazing temperature was 720 degrees, the descaling effect was average under 20MPa water pressure, the descaling rate was 82%, and there was no obvious decarburization on the surface. Because the aluminum oxide and silicon oxide content of the MG90T coating on the market is too high, reaching 1:2, the coating curing temperature is too high and the film cannot be formed at room temperature. At the same time, the SiC content in the MG90T coating is high and does not contain boron, so the film formation speed is slow and the descaling effect is average.

[0072] Figure 1 This is a surface image of the high carbon steel anti-decarburization coating provided in the embodiment of the present application and the MG90T high carbon steel coating on the market sprayed on 60Si-Cr high carbon steel before heat treatment; from the figure, it can be seen that the film formed by the high carbon steel anti-decarburization coating provided in the embodiment of the present application has a certain gloss, and the film forming rate is also very fast, while the film formed by the MG90T high carbon steel coating has no gloss, the film forming rate is relatively slow, and has a certain roughness.

[0073] Figure 2 Surface diagram of the high carbon steel anti-decarburization coating provided in the embodiment of the present application and other high carbon steel coatings on the market sprayed on 60Si-Cr high carbon steel after heat treatment and final descaling under 10MPa water pressure; from the figure, it can be seen that the high carbon steel anti-decarburization coating provided in the embodiment of the present application basically all falls off under the impact of water flow, and the descaling effect is significant, while the descaling effect of MG90T coating is average under the impact of water flow of the same size.

[0074] Figure 3 The metallographic cross-section diagrams of the high carbon steel billet workpiece treated in Example 1, the high carbon steel without coating after heat treatment and phosphorus removal, and the high carbon steel billet workpiece treated in Comparative Example 3 under optical microscope show the depth of the respective decarburization layers. The decarburization layer of the high carbon steel anti-decarburization coating provided in the embodiment of the present application is about 100um, while the decarburization layer of Comparative Example 3 reaches about 400um, and the decarburization layer of the uncoated steel reaches 500um. This shows that the high carbon steel anti-decarburization coating provided in the embodiment of the present application has certain anti-decarburization performance.

[0075] For matters not mentioned above, the prior art applies.

[0076] Although some specific embodiments of the present invention have been described in detail through examples, those skilled in the art should understand that the above examples are for illustration only and are not intended to limit the scope of the present invention. Those skilled in the art to which the present invention belongs may make various modifications or supplements to the specific embodiments described or replace them in a similar manner, but they will not deviate from the direction of the present invention or exceed the scope defined by the attached claims. Those skilled in the art should understand that any modifications, equivalent substitutions, improvements, etc. made to the above embodiments based on the technical essence of the present invention should be included in the protection scope of the present invention.

Claims

1. A high carbon steel anti-decarburization coating, characterized in that: The coating comprises the following raw materials in parts by weight: SiO2 is 30-35 parts, Al2O3 is 4-6 parts, talc is 0.5-1 parts, gypsum powder is 1-2 parts, ZrO2 is 1-5 parts, potassium feldspar powder is 1-3 parts, sodium feldspar powder is 1-3 parts, ZnO is 5-10 parts, Cr2O3 is 1-4 parts, SiC is 5-8 parts, B2O3 is 5-9 parts, graphite is 1-4 parts, and solvent is 30-40 parts; Among them, the Al / Si ratio is 1:6-8; The solvent consists of 0.1-0.6% methyl cellulose, 5-10% sodium silicate / potassium silicate, 0.3-1% polyethylene glycol, 0.01-0.03% sodium hexadecyl sulfate and the balance water.

2. The high carbon steel anti-decarburization coating according to claim 1, characterized in that: The density of the coating is 2.8×10 3 kg / m 3 ~3.0×10 3 kg / m 3 , and\or, the solid content is 60% to 68%.

3. A method for preparing a high carbon steel anti-decarburization coating as claimed in claim 1 or 2, characterized in that: The components are mixed and stirred according to the weight portions to obtain a powder, and the powder and the liquid are stirred until a suspension is formed to obtain the high carbon steel anti-decarburization coating; The preparation process of the liquid is as follows: after heating water, methyl cellulose, sodium silicate, polyethylene glycol and sodium hexadecyl sulfate are added in sequence, and stirred until no flocs are formed.

4. An application of the high carbon steel anti-decarburization coating as claimed in claim 3, characterized in that: The steps include: S1. Atomizing and spraying the coating on the surface of a high-carbon steel billet workpiece under a high-pressure air pump to form a coating; S2, placing the sprayed and dried high carbon steel billet workpiece into a heating furnace, first slowly heating it to a preset temperature, and keeping it warm for a period of time; S3. After the heat preservation is completed, the high carbon steel billet workpiece is taken out for descaling.

5. The use according to claim 4, characterized in that: In step S1, the thickness of the coating is 200um to 500um; or, the amount of the coating is 0.2kg / m 2 ~0.6kg / m 2 .

6. The use according to claim 4, characterized in that: In step S1, the temperature of the surface of the high carbon steel billet workpiece is 10°C to 750°C; or, the temperature of the surface of the high carbon steel billet workpiece is 30°C to 300°C.

7. The use according to claim 4, characterized in that: In step S2, the insulation temperature is a temperature within the range of 1000-1300°C.

8. The use according to claim 4, characterized in that: In step S2, in a heating furnace, the temperature is increased at a rate of 0.15-0.2°C / S, and the mixture is heated to the holding temperature and then held for 1 hour.

9. The use according to claim 4, characterized in that: In step S3, the specific operation of descaling is: use a high-pressure water gun to impact the steel billet with water for 3-5 minutes, the water pressure is 1-10 MPa, and then knock it to remove the coating material.

Citation Information

Patent Citations

  • High-temperature decarburization-preventing coating material used for spring steel

    CN102453794A

  • Oriented steel billet anti-decarburization paint, coating and preparation method thereof

    CN117511260A

Cited By

  • Anti-decarburization coating, preparation method thereof, anti-decarburization coating and application of anti-decarburization coating

    CN121087254A